TV white space for digital inclusion in Brazil - Nascimento, Matheus Freire e Silva do (2017)
This work presents a technological opportunity to make efficient use of the spectrum and at the same time shows its importance to provide digital inclusion in Brazil. The method- ology is applied in a case study investigating the area of Cear ́a, a Brazilian state, where a significant amount of spectrum that can be unleashed via TV White Space exploitation is relevant to be considered, due to its geographic and economical conditions. These white spaces can fill up some holes in the state that do not present any mobile coverage and improve the telecommunication services in other areas. The technology concept, world regulation situation and possible applications using the resource are described throughout this work. The main purpose is to use TV White Spaces together with the LTE band, as a way to soften part of the poor coverage services of 3G, 4G.